The 19th - century public woman - Dominika Eristavi - Marjanishvili, Mariam (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
The mental awakening of Georgian women and their involvement in public activities became particularly noticeable from the 1860s, which Ilia Chavchavadze termed as a significant political event, the „new age“. In the literary and public discourse of that era, when the national consciousness of the country was awakening, literary salons initiated by Georgian women emerged in a new light. Georgian women quickly became central to public opinion as they actively participated in the struggle for national liberation, the revival of their mother tongue, and theater. They also congregated around cultural hubs such as Georgian magazines and newspapers like „Droeba“, „Iveria“, „Theatre and Life“, „Georgian Library“, „Akaki Monthly Collection“, and others. Under the initiative of Georgian women writers, youth magazines, workers’ theaters, reading rooms, women’s professional schools, and women’s gymnasiums gradually took shape. Georgian women also played a significant role in politics and state administration. With the changing social structure, a new generation of women entered the arena, actively engaging in the educational system and contributing to the national progress of the country. Notable among them was Dominika Eristavi, a poet, writer, translator, the first female proofreader of the „Iveria“ newspaper, editor of the „Nobat“ magazine, politician, and founder of the „Georgian Women’s Society“, known by her literary pseudonym „Gandegili“. She was one of the active Georgian women who vehemently campaigned against the backward, restrictive views of tsarism and dedicated herself to the struggle for the rights of Georgian women. The poetess deeply believed that achieving equality for women would be the most significant factor in transforming the social structure: „A mother is the foundation of science, the backbone of family, nation, and society. A woman is the true measure of a nation’s spiritual strength. The more established and free a woman is, the more balanced society becomes, like a drop in the ocean of humanity.“ Great creative talent flourishes where women are not enslaved but free individuals. Dominika Eristavi became a symbol of Georgian women’s fight for equality, emancipation, and citizenship rights, inspiring many followers.